Synthesis of novel fluorinated building blocks via halofluorination and related reactions - Remete, Attila Márió; Novák, Tamás T.; Nonn, Melinda; Haukka, Matti; Fülöp, Ferenc; Kiss, Loránd (Beilstein Journal of Organic Chemistry, 2020)
A study exploring halofluorination and fluoroselenation of some cyclic olefins, such as diesters, imides, and lactams with varied functionalization patterns and different structural architectures is described. The synthetic methodologies were based on electrophilic activation through halonium ions of the ring olefin bonds, followed by nucleophilic fluorination with Deoxo-Fluor®. The fluorine-containing products thus obtained were subjected to elimination reactions, yielding various fluorine-containing small-molecular entities.
Keywords: fluorine; fluoroselenation; functionalization; halofluorination; stereocontrol